Graded Ferroelectrics, Transpacitors and Transponents - Mantese, Joseph V.; Alpay, S. Pamir; SpringerLink (Online service) (Boston, MA : Springer US, 2005)
Graded Ferroelectrics, Transpacitors and Transponents details the experimental and theoretical aspects of newly emerging ferroelectric devices, and their extensions to other ferroic systems such as: ferromagnetics, ferroelastics, piezoelectrics, etc. The theory and experimental results pertaining to non-homogeneous active ferroic devices and structures are presented The primary focus of the book is directed toward polarization-graded ferroelectrics and their active components - transpacitors; however, the findings here are quite general. The theory of graded ferroics is put on a solid foundation in Chapters 2 and 5, whereas much of the introductory material relies more heavily upon analogy. This was done so as to provide the reader with an intuitive approach to graded ferroics. Heterogeneous ferroics are shown as logical extensions of passive semiconductor junction devices such as p-n and n-p diodes and their active manifestations: transistors, to transpacitors, transductors, translastics and ultimately to the general active ferroic elements, transponents.
Polarization-Graded Ferroelectrics: The Dielectric Analogues of Semiconductor Junction Devices -- Thermodynamic Theory of Polarization-Graded Ferroelectrics -- Graded Ferroelectric Devices (GFDs) -- Trans-capacitive Devices: Transpacitors -- Graded Ferroics and Transponents.
Keywords: Materials science; Condensed matter; Optical materials; Electronic materials; Materials -- Surfaces; Thin films; Materials Science; Surfaces and Interfaces, Thin Films; Optical and Electronic Materials; Ceramics, Glass, Composites, Natural Methods; Condensed Matter Physics; Characterization and Evaluation of Materials; Electronic books